Urinary biomarkers for the early prediction of bronchopulmonary dysplasia in preterm infants: A pilot study - Cui, Xuewei; Fu, Jianhua (Frontiers in Pediatrics, 2022)
Background: This study investigated whether 8-hydroxy-2′-deoxyguanosine (8-OHdG) and N-terminal pro-brain natriuretic peptide (NT-proBNP) concentrations in the urine could predict bronchopulmonary dysplasia (BPD) in preterm infants. Methods: This prospective cohort study enrolled 165 preterm infants, of whom 70 developed BPD. We measured urinary 8-OHdG and NT-proBNP concentrations from day of life (DOL) 7 to 28. Then, we evaluated the prediction efficiency by receiver operating characteristic curves and assessed correlations between the two biomarkers. Finally, we identified the predictive risk factors for BPD by multivariable logistic regression. Results: 8-OHdG and NT-proBNP levels were significantly higher from DOL 7 to 28 in the BPD group than in the control group (P <0.05). Additionally, the 8-OHdG level was positively correlated with the NT-proBNP level (r: 0.655–0.789, P <0.001), and the 8-OHdG and NT-proBNP levels were positively correlated with mechanical ventilation duration and oxygen exposure time (r: 0.175–0.505, P <0.05) from DOL 7 to 28. Furthermore, the 8-OHdG (DOL 14 to 28) and NT-proBNP (DOL 7 to 28) levels were significantly associated with BPD development (P < 0.05). Conclusion: The urine 8-OHdG concentrations from DOL 14 to 28 and NT-proBNP concentrations from DOL 7 to 28 may be practical noninvasive predictors of BPD development in preterm infants.